Spondylodiscitis After Surgery for Pelvic Organ Prolapse: Description of a Rare Complication and Systematic Review of the Literature - Stabile, Guglielmo; Romano, Federico; Topouzova, Ghergana A.; Mangino, Francesco Paolo; Di Lorenzo, Giovanni; Laganà, Antonio Simone; De Manzini, Nicolò; Ricci, Giuseppe (Frontiers in Surgery, 2021)
Background: Spondylodiscitis can be a rare complication of gynecological surgery, typically of procedures involving the sacrum and the sacrospinous ligament. This report presents a case of spondylodiscitis arising after a laparoscopic sacrocolpopexy with a mesh. We also review the literature finding 52 cases of spondylodiscitis following sacrocolpopexy and (or) rectopexy with or without a mesh. Methods: We performed a comprehensive search from the electronic databases MEDLINE (Pubmed), Scopus, Web of Science, Embase, CINAHL and Google Scholar from 1990 to February 2021 in order to identify case reports or case series reporting on spondylodiscitis after rectopexy or sacrocolpopexy. Results: We identified 52 total post-operative spondylodiscitis. We examined the mean age of patients, the surgical history, the time from initial surgery to spondylodiscitis, the presenting symptoms, the diagnostic tools, the medical and surgical treatment, the type of mesh used, the surgical access and the possible causes of spondylodiscitis. Conclusions: Diagnosis of spondylodiscitis may be challenging. From our review emerges that recurrent pelvic pain and lumbosciatalgia may be signals of lumbar spondylodiscitis. Magnetic resonance is the gold standard examination for spondylodiscitis. Surgical practice needs to be improved further in order to establish the best procedure to minimize the incidence of this complication. Awareness of symptoms, timely diagnosis and treatment are fundamental to prevent irreversible complications.